2015
DOI: 10.1111/ajps.12173
|View full text |Cite
|
Sign up to set email alerts
|

Rising to the Top: Gender, Political Performance, and Party Leadership in Parliamentary Democracies

Abstract: Party leaders are the main actors controlling campaign strategies, policy agendas, and government formation in advanced parliamentary democracies. Little is known, however, about gender and party leadership. This article examines gendered leadership patterns across 71 political parties in 11 parliamentary democracies between 1965 and 2013. It shows that men and women have different access to, and experiences in, party leadership and that these gendered political opportunity structures are shaped by parties' po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
156
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(170 citation statements)
references
References 67 publications
1
156
2
1
Order By: Relevance
“…Consequently, women are excluded from resources and positions of power (Barnes ). Women are less likely to be placed on powerful committees, hold fewer leadership positions in legislative bodies, and rarely preside over committees (O'Brien ; Thomas and Welch ; Towns ). Women may also be excluded from informal networks of power, not invited to important social events, or others may fail to provide them with strategic information at a time when it may be useful (Barnes ; Rosenthal ).…”
Section: Influences On Legislative Collaborationmentioning
confidence: 99%
“…Consequently, women are excluded from resources and positions of power (Barnes ). Women are less likely to be placed on powerful committees, hold fewer leadership positions in legislative bodies, and rarely preside over committees (O'Brien ; Thomas and Welch ; Towns ). Women may also be excluded from informal networks of power, not invited to important social events, or others may fail to provide them with strategic information at a time when it may be useful (Barnes ; Rosenthal ).…”
Section: Influences On Legislative Collaborationmentioning
confidence: 99%
“…On the one hand, party ideology is a crucial determinant of women's representation, with left parties being more responsive to group representation demands through the use of gender quotas (Kittilson 2006). Yet, whereas cabinets led by left parties tend to be more feminised (Claveria 2014), in the case of top executive positions the effect of party ideology is inconclusive (O'Brien 2015;Wauters & Pilet 2015). Right-wing parties, which usually reject positive action, often apply a 'compensatory' strategy through which a significant proportion of women are placed in top positions (Simón & Verge 2017).…”
Section: Organisational Factorsmentioning
confidence: 99%
“…The scarce literature on reselection at the top executive level indicates that incumbency is the most prominent factor. This notwithstanding, research on gender and political parties has shown that female party leaders have a greater likelihood of stepping down when their parties lose vote share (O'Brien 2015;O'Neill & Stewart 2009). Loser candidates also tend to get another shot when being the party leader (Astudillo 2015).…”
Section: Reselectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, there are several party‐level characteristics that could also explain variation in women's representation. First, we control for the gender of the party leader at the time of the election (via a dummy variable), and hypothesise that a female party leader could support other women running for office, including for a seat in Brussels and Strasbourg (O'Brien )…”
Section: Variables and Datamentioning
confidence: 99%